Performance of fiber reinforced clayey sand composite - Chegenizadeh, A; Nikraz, Hamid (Gaodeng Jiaoyu Chubanshe, 2012)
Soils and their related behavior have always been the subject of many studies. Recent researches showsome interests in investigation of inclusion of randomly distributed fiber in soil. This study focuses on effect of fiber inclusion on the strength and other parameters of clayey sand composite material. First part of this study is related to effective parameters on strength of the clayey sand composite with using natural fiber and plastic fiber and different fiber contents and length. Triaxial consolidated undrained (CU) tests were carried out to investigate behavior of the composite under different condition. The fiber percentage varied from 0% (for unreinforced samples) to 4% and fiber length varied from 8 to 25 mm. The fiber length and fiber content found to play important rule on the strength of fiber reinforced composite.